Pengaruh Kualitas Pelayanan Kefarmasian terhadap Kepuasan, Kepercayaan, & Loyalitas Konsumen Apotek - Dianita Rifqia Putri (Universitas Muhammadiyah Ponorogo, 2017)
There is a shift in the orientation of pharmacy services from the only drug management to the comprehensive service to patients (Pharmaceutical Care), In line with the development of science and technology in the field of pharmacy. Some of the factors that influence consumer loyalty are the satisfaction and trust. The method of this study was purposive sampling method spreaded on 120 respondents. The validity test of the questionnaire carried out by factor analysis and reliability test was conducted using Cronbach's Alpha. The data analyzed by using SEM-PLS (Structural Equation Modeling-Partial Least Square). Results of this research showed that quality of pharmacy services has a positive effect (P-Value is 0.02 and the value of Path Coefficient = 0.369) to pharmacies consumer satisfaction. The quality of pharmacy services has a positive effect (P-Value of .01 and the value of Path Coefficient = 0.292) to the pharmacy consumer trust. Pharmacy customer satisfaction has a positive influence (P-Value of .01 and the value of Path Coefficient = 0.338) to the trust of pharmacies consumer. Pharmacy customer satisfaction has a positive influence (P-Value of .01 and the value of Path Coefficient = 0.313) on consumer pharmacies loyalty. Trust of consumer pharmacies has a positive effect (P-Value of .01 and the value of Path Coefficient = 0.381) on consumer pharmacies loyalty.